Toxic metals in Loggerhead sea turtles (Caretta caretta) stranded freshly dead along Sicilian coasts. Issue 1 (31st December 2023) - Cammilleri, Gaetano; Galluzzo, Francesco Giuseppe; Pulvirenti, Andrea; Pantano, Licia; Calabrese, Vittorio; Gentile, Antonino; Cumbo, Valentina; Macaluso, Andrea; Macaluso, Vito; Vella, Antonio; Ferrantelli, Vincenzo
Abstract: Background: The Loggerhead sea turtle ( Caretta caretta ) is a marine reptile belonging to a monophyletic group of chelonians. As these animals are long-lived, they have the ability to accumulate pollutants. Aim: To collect epidemiological data on toxic metals in marine Loggerhead sea turtles. Materials and Methods: Forty Loggerhead sea turtles comprising 25 males and 15 females stranded freshly dead between 2013 and 2018 along the coasts of Sicily, Southern Italy, were examined for arsenic, cadmium, and lead accumulation in muscle and adipose tissues by means of a validated ICP-MS method. A modified K index as a growth condition factor, namely Fulton's K index, was used. Samples were tested in duplicate. A Wilcoxon rank sum test was carried out to evaluate metal contents differences between muscle and adipose tissues and between genders. Results: The Fulton's K index suggested a good body condition of the C. caretta recovered with mean values of 5.34 ± 3.40 ( n  = 40; ±SD). Detectable concentrations of lead were found in 70% of the samples analysed with mean values of 0.65 ± 1.67 mg/kg wet weight and 0.51 ± 1.29 mg/kg wet weight in muscle and adipose tissues, respectively. No significant differences in arsenic, cadmium, and lead were detected between genders. In addition, no significant correlation was found between modified K index and concentrations of arsenic, cadmium, and lead. Clinical relevance: Findings on muscle and adipose tissues suggest chronic exposure of Caretta caretta to high concentrations of especially lead which might negatively affect health and welfare of these marine turtles although body condition was good.